Pengelolaan Sarana Air Minum (SAM) rumah tangga yang aman di Padang Gelugur Pasaman, Sumatera Barat - Risna Nofriani; Yusni Ikhwan Siregar; Bayhakki Bayhakki (EcoNews, 2023)
The global target that must be achieved regarding universal and equitable access to safe and affordable drinking water for all is the Sustainable Development Goals (SDGs) Goal 6, namely that universal access to safe drinking water fulfills the 4K. Namely quantity, quality, continuity, and affordability, and all households have access to adequate sanitation. According to the SDGs, safe drinking water is drinking water that is fit for consumption and free from fecal contamination and certain chemicals. Water quality at the point of consumption is strongly influenced by drinking water management factors at the household level, such as processing, storage and storage factors for raw water or drinking water sources. This research was conducted in October 2022, the sample in this study was the community as many as 98 respondent. In terms of quantity, the basic needs for water (food and drink) have been fulfilled, in terms of the quality of drinking water they have not been met, in terms of continuity they have been fulfilled, and in terms of affordability it is affordable in terms of distance, but not yet affordable in terms of price. The lack of quality and affordability can be met by adding free drinking water facilities and using rainwater.